Pemberdayaan UKM Jamaah Masjid berbasis Digital Marketing di Desa Tlogoadi Kecamatan Mlati Kabupaten Sleman - Andhika Giri Persada; Siti Achiria (Penerbit Goodwood, 2022)
Purpose: The purpose of this paper is to present a community service that aims to empower SMEs during the Covid-19 pandemic through digital marketing. Method: The method used in this community service is Focus Group Discussion, consultation, and practice. Result: Community empowerment about digital marketing has been able to provide knowledge and practices related to online marketing innovations for SMEs, so that it can become a discourse for SMEs to sell their products online. SMEs know the benefits and are able to apply several techniques and supporting tools in digital marketing and understand the concepts of Islamic economics. The artifacts produced from this community service are in the form of social media accounts that are in accordance with digital marketing principles. Conclusion: The synergy framework between SMEs and a supporting team consisting of young people who are active in mosques, is important, because SMEs will be more optimal in utilizing digital marketing in selling online. The program carried out with the Takmir institution has a positive impact as a solution to the problems of SMEs during the pandemic. Thus the mosque is no longer only used as a place of worship, but also as a center for community economic growth.